Physico-chemical Properties of Effluents Discharged from Different Industries of Gazipur, Bangladesh and its Suitability for Agricultural Land (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted to assess physical parameters, major ionic constituents and trace metals content at Gazipur area to know the quality of effluent during March in 2013 for irrigation usage. The pH of collected effluent samples were almost neutral but in case of TDS values all the samples were suitable for irrigation where considering EC values almost harmful for irrigation. The anion i.e. in case of CO3, SO4 and PO,sub>4 all the collected effluent samples were suitable for irrigation but in case of almost Cl values and all HCO3 values unsuitable for irrigation. Similarly, the cation i.e. in case of Na, Mg, Ca and K all the collected effluent samples were suitable for irrigation. Among the studied trace metals (Fe, Zn, Cu, Pb, Cd and Mn) all of the collected effluent samples were suitable for irrigation except two samples for Mn and Cu. On the other hand, in case of SAR most of the samples were excellent category but in case of SSP most of the samples were graded as doubtful and in case of RSC and hardness most of the samples were unsuitable class for irrigation purposes. So to protect the agricultural land whole of the study area a pollution free technology such as Effluent Treatment Plants (ETP) to each industry should be established.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22165 J. Environ. Sci. & Natural Resources, 7(1): 157-167 2014